Faktor-faktor pemasaran yang mempengaruhi kesetiaan pengguna dalam menggunakan produk kesihatan herba tempatan di Malaysia - Ari Husaini, Hamdan (2014)
Marketing activities of herbal health products in Malaysia have shown significant growth since the last few decades. The intensifying growth has triggered several questions about the actual potential of marketing to continuously expand despite moderate consumer loyalty on the local health products. The importation of foreign health products into the domestic market and various issues related to local health products marketing activities, seem to be among the key reasons why consumer loyalty on local health products deteriorated. In relation to this, the present study intended to examine the relationship between consumer loyalty with marketing mix (product, price, place of distribution and promotion) and consumer knowledge. The study was conducted in University Utara Malaysia and the respondents were both the academic and administrative staff in three different colleges i.e. COB, COLGIS and CAS. The sample size of this study is 330 samples. This study used SPSS 19.0 to analyze the data. The findings revealed that all five hypotheses were supported and all the independent variables namely product, price, place of distribution and promotion, and consumer knowledge were significantly and positively related to consumer loyalty. The detail of the discussions is provided in the study.